Evaluating energy efficiency from the perspective of clean energy and carbon emission - Chen, Bin; Dai, Yao; Ye, Junhao; Xu, Huan; Huang, Yanlu; Bie, Pei (Frontiers in Environmental Science, 2022)
Improving energy efficiency and optimizing energy structure is the key to achieving the “dual carbon” goal and high-quality development. This paper calculates the energy efficiency of 30 provinces in China between 2000 and 2017 using the DEA method. The study found that in China, the energy efficiency is higher in East China than in West China, in South China than in North China, and in the coastal areas than in the interior. Moreover, the efficiency gap between clean fuel and fossil fuel is widening. Taking total power consumption as energy input and measuring carbon emissions using regional grid base line emission factor can accurately measure China's clean energy efficiency. The conclusions of the study provide important references for promoting China’s energy transformation and the development of the green economy.